Perspectivas de uma política da convivência em Hannah Arendt : os direitos humanos como possibilidade de intersecção político-teológica problematizados pelo pensamento de Hannah Arendt - Oliveira, Kathlen Luana de (2009)
This research is a political approach to human rights in intersection with theology, in the rescue of the genesis of human rights as a historical construction, in the confrontation with violence and in the political perspective of living together, based on Hannah Arendt's thought. The first part places theology in the political debate concerning human rights, without basing them on the theological thought, centralizing, thus, the political density of human rights. It evidences limits and potentialities of the intersection between theology and politics, based on the understanding of theology as "wisdom transfigured by love" and as "pathetic theology". It establishes a dialogue between Jürgen Moltmann's political perception and Hannah Arendt s analysis of the theological tradition. The second part approaches human rights as a historical construction in the sphere of a political community and reiterates the fact that human rights do not come from the naturalization of dignity or of human equality. The origins of human rights and the differences are presented in its positivist period exposed in the Declaration of Independence of the United States of America and in the Declaration of Rights of Man and Citizen, evidencing that not all people were recognized as equals and holders of rights. Human rights integrate the public space and demand freedom and emancipation against oppression and violence, as long as they are guaranteed and protected by a political community. The third part attests that violence invades the public sphere, revealing the unfeasibility of human rights. The violence of the twentieth century disabled the right of having rights, the right of belonging to a political community, the right of building a home. The understanding of violence, associated with politics reduces the power to relationships of dominance and relationships based on fear, destroying human plurality, disabling the action in concert. The fourth part points towards human rights as indispensable references for the establishment of a common world, ruled by living together and characterized by the valorization and the recognition of human plurality, emphasizing the importance of the power of forgiving, of promising and the possibility to begin. In spite of the destruction of the common world, in which consumers, violence, and reflexive emptiness prevail, there are possibilities of new beginnings. The hope comes from the birth rate, from the relationship among singular people and from the possibility of resistance which encourages action. Amid the destruction of everything that exists among people, human rights carry possibilities of living together and begin movements of resistance. Through this construction process, human rights reveal that the idea of belonging to the world needs to be rescued, firstly, as common sense, and, secondly, human rights reveal that belonging to the world is the right of turning it a home, not a desert. Therefore, the human rights possess possibilities to promote the living together, contradicting the conditions of the current politics.